El desarrollo de la creatividad en el aula y su incidencia en el aprendizaje de los niños y niñas de primer grado de educación general básica de la unidad educativa fiscal Quito Sur de la ciudad de Quito, período lectivo 2013-2014 - Rodríguez Jijón, Johanna Manuela (2014)
This thesis refers to: THE USE OF CREATIV AND THEIR INFLUENCE ON THE LEARNING DEVELOPMENT OF CHILDREN OF SCHOOL, FIRST DEGREE GENERAL EDUCATION BASIC EDUCATION TAX UNIT " SOUTH QUITO " QUITO CITY , PERIOD 2013 - 2014 , made according to the provisions of the Academic Regulations of the National University of Loja. Was raised as General Purpose: Raise awareness among teachers of School , First Grade General Education Basic Education Unit Attorney " Quito Sur " of the city of Quito , on the importance of Puppets in the Oral Language Development . The methods used for the preparation of this research work were : Scientist , Inductive- Deductive , Analytic - Synthetic and Statistical Model , the same that were used to efficiently achieve the goal. The techniques and instruments used were: A Survey applied to teachers of School , First Grade General Education Basic Education Unit Attorney " Quito Sur " to establish Puppets Types used with children in the workday work, and an Observation targeted at girls and boys High School , First Grade General Education Basic Education Unit Attorney " Quito Sur " , to assess the Learning Development. We conclude that : 100% of the teachers surveyed said that the type of puppets used with children in the daily work is the glove puppet , that within the puppet is the most known and traditional , they can manipulate placing his hand inside , and , thanks to its use can be achieved in children with a free and natural expression of their thoughts and ideas , overcoming shyness dramatically through its entertainment, it is the ideal resource to capture their attention , blocking all his fears , fears , anger, hate, etc. . The 48 % of children have an Oral Language Development Highly Satisfactory, Satisfactory , 43% , and 9% Unsatisfactory . The Oral language is a result of a process of imitation and maturation through the wealth of stimuli that exist in the environment , as a need to exchange ideas , reflect and create new knowledge , hence the importance of children receive constant stimulation to improve their speaking , reading through stories, etc